Analisis Efektivitas Pencapaian Target Pendapatan Asli Daerah - Haninun HANINUN; Mauli Luzia Eka Safitri (Jurnal Akuntansi dan Keuangan, 2015)
33 provinces and 471 districts / cities in Indonesia, only about 10 percent of which have aformal setting boundaries one Lampung province has 15 districts / cities. Lampung Province has other sources of income and abundant natural resources in each region. Therefore, this study aims to demonstrate empirically the effectiveness of Local Revenue Target Achievement At Regency / City in Lampung. The object of this study was 15 District / City in the province of Lampung. The data used in this study is that the data collected in 2010 to 2012. The data analyzed in this study are secondary data obtained from documents Budget Realization Report Regency / City in Lampung Province obtained from the Board of Finance of the Republic of Indonesia Representative Pemerika Lampung Province. Budget Realization of this report was obtained data on the number of actual revenue (PAD). The sampling method using census method by taking the entire population. From these data, then analysis by using the calculation of the ratio of the degree of decentralization, the ratio of financial independence and effectiveness ratio. The results of this study indicate that the Budget Actual revenue (PAD) Lampung Province from 2010-2012 has been very effective. That means the regional government to realize the budget revenue (PAD) properly.